Sustained outcomes of a peer-taught family education program on mental illness - Lucksted, A.; Medoff, D.; Burland, J.; Stewart, B.; Fang, L. J.; Brown, C.; Jones, A.; Lehman, A.; Dixon, L. B. (Acta psychiatrica Scandinavica, 2013)
Objective:  This study examines 6‐month follow‐up data from participants in a randomized trial of a peer‐driven 12‐session family support and education program, called family‐to‐family (FTF) and offered by the US National Alliance on Mental Illness, to determine whether improvements in distress, family functioning, coping and empowerment were sustained. Method:  Individuals randomized to the FTF condition were assessed after program completion and then 3 months later on measures of distress, family functioning, coping, and empowerment. We used a multilevel regression model (sas proc mixed) to test for significant changes over time (baseline, 3 and 9 months). Results:  All significant benefits that FTF participants gained between baseline and immediately post‐FTF were sustained at 9 months including reduced anxiety, improved family problem‐solving, increased positive coping, and increased knowledge. Greater class attendance was associated with larger increases in empowerment and reductions in depression and displeasure with ill relative. Conclusion:  Evidence suggests that benefits of the FTF program were sustained for at least 6 months without any additional boosters or supports. Peer‐based programs may produce sustained benefits for individuals seeking help in addressing challenges and stresses related to having a family member with a mental illness.